2023
DOI: 10.21203/rs.3.rs-2407050/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The efficacy and safety of an intranasal spray COVID-19 vaccine in a randomized double-blind placebo-controlled phase Ⅲ trial during Omicron period

Abstract: The live-attenuated influenza virus vector-based intranasal vaccine (dNS1-RBD, Pneucolin®) is the world’s first COVID-19 mucosal vaccine to enter human trials, and has been issued for emergency use authorization in China. Here, we report safety and efficacy data from a multi-centre randomized, double-blind, placebo-controlled phase 3 clinical trial of Pneucolin® (two doses, 14 days apart) in adults (18 years and older) during the Omicron circulation. The result showed a favorable safety profile, with no differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In phases I and II clinical trials, the vaccine demonstrated an immunogenicity pattern that was highly consistent with animal studies-a weak peripheral immune response 20 . In recent phase III clinical trial results, this intranasal COVID-19 vaccine exhibited an encouraging efficacy combined with great safety profiles in the elderly or population with underlying chronic disease 21 . Thrillingly, this vaccine was approved for emergency use in China on December 2, 2022, named Pneucolin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In phases I and II clinical trials, the vaccine demonstrated an immunogenicity pattern that was highly consistent with animal studies-a weak peripheral immune response 20 . In recent phase III clinical trial results, this intranasal COVID-19 vaccine exhibited an encouraging efficacy combined with great safety profiles in the elderly or population with underlying chronic disease 21 . Thrillingly, this vaccine was approved for emergency use in China on December 2, 2022, named Pneucolin.…”
Section: Discussionmentioning
confidence: 99%
“…We previously developed an intranasal vaccine based on the NS1-deleted H1N1 vector carrying the gene encoding SARS-CoV-2-RBD (dNS1-RBD) 19,20 . A randomized placebo-controlled phase III clinical trial demonstrated that the vaccine has a good safety and broad-spectrum efficacy against Omicron symptomatic infection 21 [ChiCTR2100051391], and was approved for emergency use in China on December 2, 2022, named Pneucolin. This vaccine prevents COVID-19 induced by Prototype, Beta and Omicron of SARS-CoV-2 challenge in hamster models in the absence of detectable neutralizing antibodies 19 .…”
mentioning
confidence: 99%
“…The positive results of the Phase 3 clinical trial for this vaccine may help improve the vaccine confidence of the public, which have been posted as a preprint on Research Square after our study period. 20 …”
Section: Discussionmentioning
confidence: 99%
“…18 The phase III clinical trial also shows that this vaccine is well-tolerated and can be an antibody-independent broad-spectrum effective tool to combat SARS-CoV-2 variants. 19 , 20 This vaccine is applicable for people 18 years of age and older, including those who have not been immunized against any COVID-19 vaccine, and those who have received one, two, or three previous doses of other COVID-19 vaccines according to the vaccine instruction.…”
Section: Introductionmentioning
confidence: 99%